Effects of antioxidant supplementation on exercise performance in acute normobaric hypoxia - Mariacher, C.; Gatterer, H.; Greilberger, J.; Djukic, R.; Greilberger, J.; Philippe, M.; Burtscher, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Background/Objectives: To compare the effects of a 3-week supplementation between two different mixtures of antioxidants and placebo on aerobic exercise performance in acute normobaric hypoxia. Subjects/Methods: Seventeen subjects were randomly assigned in a double-blind fashion to receive a broad-based antioxidants supplement containing beta-carotene, ascorbic acid, d-alpha-tocopherol-succinate, N-acetylcysteine, ribo- flavin, zinc, and selenium (antioxidant capsule group [AO group]), or a combination of alpha-ketoglutaric acid (á-KG) and 5-hydroxymethylfurfural (5-HMF; CYL concentrate supplementation group [CS group]), or placebo (PL group). Before and after supplementation, subjects performed two incremental cycle-exercise tests until exhaustion. The first test was conducted under normoxic conditions (LA, FiO2 of 20.9%, ~547 m) and the second after the 3-week supplementation period under normobaric hypoxic conditions (AHA, FiO2 of 12.9%, ~4300m). Results: In CS peak cycling performance (peak power) declined from LA to AHA 7.3% (90% CI: 2.2-12.4) less compared with PL (p = .04) and 6.7% (90%CI: 3.2-10.2) less compared with AO (p = .03). Better maintenance of aerobic exercise capacity in CS was associated with an attenuated reduction in maximal heart rate in hypoxia. Conclusions: Aerobic exercise performance was less impaired in acute normobaric hypoxia after 3 weeks with supplementation of á-KG and 5-HMF compared with a broad-based antioxidants supplement or PL.